Do Not Dismiss Outsourcing : Provide the Best Solution for the Sake of the Nation - Junaedi Junaedi (International Forum of Researchers and Lecturers, 2025)
The current criminal law system is still oriented towards the perpetrator, with minimal protection for victims. Ideally, the law should prioritize justice for victims through a criminological and victimological approach. Therefore, legal reform, officer training, and integrated services are needed so that crime prevention is more effective and just. This study aims to explore the transformation of criminological and victimological perspectives that can be the basis for developing a crime prevention strategy based on victim protection.method uses a descriptive qualitative approach to explore the transformation of criminology and victimology perspectives in crime prevention strategies based on victim protection. Data were collected through literature studies and analyzed thematically. The results are expected to provide conceptual and practical recommendations to strengthen the legal system and social policies that are responsive to victims.The results of this study show that the transformation of criminological and victimological perspectives reflects a shift from a perpetrator-centric legal approach to a more holistic and victim-centric one. This integration strengthens the legal system and social policies to better protect, restore and empower victims, and to develop effective crime prevention strategies. With a more humane and restorative justice approach, this transformation becomes an important foundation for reducing crime rates and forming responsive and sustainable public policies.